Pakchoy farming income based on passive and active hydroponic methods - Wiyono, Sulistyodewi Nur; Permadi, Nida Fathi; Djuwendah, Endah; Trimo, Lucyana; Rochdiani, Dini; Wulandari, Eliana (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2021)
The decrease of agricultural land becomes one of the problems in farming. Hydroponic system is one of the alternatives that can be the solution of the problem. The hydroponic system is divided into two methods, i.e. the active hydroponic system and the passive hydroponic system. This study described the income analysis of the active and passive hydroponic systems and investigated which system was more profitable. This research was conducted in two companies that have similar business scale, namely the BA corp., for passive hydroponic system and the Nb Farm for active hydroponic system, in which they were located in the Lembang, West Bandung. In the calculation of BC ratio, active hydroponic system is declared feasible, indicating that the hydroponic farming carried out by Nb Farm is profitable and feasible to be conducted. The results of this study indicate that the active hydroponic system has a greater advantage than the passive hydroponic system in pakchoy farming.